Hydrogen gas as a central on-off functional switch of reversible metabolic arrest - New perspectives for biotechnological applications - Zerveas, Sotirios; Kydonakis, Evaggelos; Mente, Melpomeni-Sofia; Daskalakis, Vangelis; Kotzabasis, Kiriakos (My University, 2021)
Metabolism is the sum of all chemical reactions that sustain life. There is an ongoing effort to control metabolic rate, which correlates with the maximum lifespan potential and constitutes one of the oldest scientific questions. Herein, we report on the complete reversible arrest of cellular metabolism and cell growth in a series of organisms, from microalgae to yeast upon exposure to a 100 % hydrogen atmosphere. We also report a tolerance of the microalgae under these conditions against extreme stress conditions, like high salt concentrations. The addition of oxygen or air almost completely restores the metabolic rate and cell growth. Molecular dynamics simulations are employed to decipher this phenomenon at atomic scale. Various proteins, including photosynthetic and respiratory complexes (LHCII, cytochrome c5) are probed in the interaction with hydrogen. Exposure to hydrogen, as opposed to oxygen, decreases the fluctuations of protein residues indicating thermostability. According to the above mechanism, an absolute hydrogen atmosphere can preserve biological products (e.g. fruits) for a long time without consuming any energy. By combining biological, chemical and computational methods, in this research we provide the basis for future innovative studies and advances in the field of biotechnology.
Keywords: Biological products preservation; Computational biology; Hydrogen; Photosynthesis; Protein stability; Reversible metabolic arrest